Psychometric Properties of the Arabic Version of the Perceived Physical Ability  Scale for Children in Oman - Sabry M. Abd- (Sultan Qaboos University, 2014)
This study aimed at examining the psychometric properties of the Perceived Physical Ability Scale for Children (PPASC) within an Omani context. A sample of 250 fourth graders (130 males and 120 females) from six public primary schools in four governorates in Oman responded to Arabic translated version of the PPASC. Data on students' in-class physical activity, social desirability, and teachers' nominations of students' physical ability were also collected. Confirmatory factor analysis revealed that the unidimensional model of the PPASC had adequate fit to the data. Multigroup CFA revealed gender invariance for PPASC unidimensional model when it was compared across male and female groups. A latent mean analysis showed that there were significant gender differences in perceived physical ability favoring males. The PPASC correlated positively with in-class physical activity and teachers' nominations of students' physical ability but not with social desirability.